Learning theories in childhood - Gray, Colette; MacBlain, Sean (Los Angeles : SAGE, 2015)
Focusing on the early philosophies of learning and key behavioural, cognitive, and social theorists, including Locke, Rousseau, Montessori, Piaget, Vygotsky, Bandura, Bronfenbrenner and Bruner, this popular book provides a comprehensive overview of children's learning.
1. An introduction to learning theories -- 2. The developmental processes underpinning learning : the role of theory and philosophy -- The developing brain -- Definitions of learning -- Learning styles -- Unpacking philosophy and theory -- Philosophy and learning -- Understanding theory -- 3. The founding fathers and philosophies of learning -- John Locke and the empiricists -- Jean-Jacques Rousseau and the essence of being born "good" -- Friedrich Froebel and the emergence of the kindergarten -- John Dewey and the debate around child-centered education -- Maria Montessori and the nature of children -- Rudolf Steiner and Steiner Waldorf schools -- Rachel and Margaret McMillan and the founding of the Nursery School Movement -- 4. Classical and operant conditioning : the early years experience -- Pavlov and classical conditioning -- Watson and behaviourism -- Learning through trial and error -- Behaviour has consequences -- Enhancing motivation -- 5. Piaget, learning and cognitive constructivism -- Stages of development -- Sensorimotor state (0-2 years) -- Pre-operational stage (2-7 years) -- Concrete operational stage (7-11 years) -- Formal operational stage (11-15 years) -- Schema formation -- Criticism of Piaget's theory -- Piaget in the early years setting -- 6. Vygotsky : learning in a social matrix -- Vygotsky and social constructivism -- Culture and society -- Developing language and thought -- Play, creativity and thought -- The zone of proximal development : walking "a head taller" -- Peer collaboration -- Criticisms of Vygotsky -- Vygotsky in action -- Golden Key Schools -- 7. Bandura, Bronfenbrenner and social learning -- Bandura's social learning theory -- Bronfenbrenner's ecological systems model -- 8. Bruner and discovery learning/constructivism -- Burner in context -- What do we mean by learning -- How children represent the world -- The importance of language -- Bruner's views on education -- Connecting with Bruner in the 21st century -- 9. New perspectives : childhood studies -- The evolution of a new theoretical paradigm -- Methods and methodologies -- Giving voice to the child -- Criticisms of the new social studies of childhood -- 10. Theory in practice : learning and the reflective practitioner -- Becoming a reflective practitioner -- Developing young learners -- Creating effective learning environments -- Putting theory into practice -- 11. The changing nature of learning -- Childhood in the 21st century -- Changing landscapes in the early years -- Changing landscapes in the primary years -- Emerging literacies -- How play and children's interests are changing and impacting upon learning -- Glossary.
Includes bibliographical references and index.
BIED
Keywords: Learning; Learning, Psychology of; Learning, Psychology of; Learning